In vitro regeneration of bakawali (Epiphyllum oxypetalum) / Asmah Awal … [et al.] - Awal, Asmah; Abdullah, Shamsiah; Baba, Abdul Razak; Muda, Nazatul Asikin; Osman, Nurul Izzati (Research Management Institute (RMI), 2013)
Being a tropical country with a large portion of rainforests, Malaysia is blessed by having various types of exotic plants and herbs. Among those precious species is bakawali which is scientifically known as Epiphyllum oxypetalum. Bakawali belongs to Cactacea family and is also commonly known as ric rac cactus, kengwa, queen of the night, lady of the night and tan hua (Ariffin, 2005; Chooi, 2006). Efficient in vitro regeneration of bakawali under controlled environment determines the competency of plant tissue culture techniques in horticultural industry development. Micropropagation of bakawali is also an important step of any genetic transformation and improvement protocol because it provides sources of starting materials that can be used in genetic studies for its improvement. A proper manipulation and determination of plant growth regulators in plant tissue culture can induce embryogenesis, organogenesis and rhizogenesis of plant tissues by varying the cytokinin-to-auxin ratio in the culture media. The present study was carried out with the aim of establishing in vitro regeneration protocol of bakawali (£ oxypetalum). Lateral buds obtained from three different sections of young bakawali leaves were used as explants. A micropropagation method using culture media supplemented with various plant growth regulators (NAA and BAP) was demonstrated.